On the family Sphyraenidae (Actinopterygii: Perciformes: Scombroidei) in Baía de Todos os Santos and Ilha de Itaparica (Bahia) - Lopes , Paulo R. D.; Oliveira-Silva, Jailza Tavares de (SITIENTIBUS série Ciências Biológicas, 2002)
The species of the family Sphyraenidae from Baía de Todos os Santos and Ilha de Itaparica (littoral of the state of Bahia) were recorded based on specimens deposited in collections of Laboratório de Ictiologia (Universidade Estadual de Feira de Santana) and Museu Nacional (Universidade Federal do Rio de Janeiro). Only two species, presently known to Brazilian coast, were identified: Sphyraena barracuda (Walbaum, 1792) and S. guachancho Cuvier, 1829.